Implementation of initiatives to prevent student stress: process evaluation findings from the Healthy High School study. Issue 3 (27th March 2020) - Bonnesen, Camilla Thørring; Jensen, Marie P; Madsen, Katrine R; Toftager, Mette; Rosing, Johanne A; Krølner, Rikke F
Abstract: Process evaluation of public health interventions is important for understanding intervention results and can help explain why interventions succeed or fail. This study evaluated implementation of a school-based intervention combining educational and environmental strategies to prevent stress among Danish high school students. We investigated dose delivered, dose received, fidelity, appreciation, barriers and facilitators at the 15 intervention schools using mixed methods and multiple data sources: questionnaires among students, teachers and school coordinators; semi-structured interviews with school coordinators; telephone interviews with student counsellors; and focus group interviews with students and teachers. Implementation varied by schools and classes. Half of the intervention schools delivered the environmental strategies. For the educational strategies, dose delivered differed according to intervention provider. Students reported a lower dose received compared with dose delivered reported by school staff. Overall, student counsellors, school coordinators and students—especially those with low perceived stress—were satisfied with the stress preventive initiatives while teacher satisfaction varied. Five main barriers and three facilitators for implementation were identified. The use of multiple data sources and data methods created new knowledge of the implementation process which is important for the interpretation of effect evaluation and development of future interventions.